A Unified Approach for the Total Synthesis of cyclo‐Archaeol, iso‐Caldarchaeol, Caldarchaeol, and Mycoketide. (4th June 2021) - Andringa, Ruben L. H.; de Kok, Niels A. W.; Driessen, Arnold J. M.; Minnaard, Adriaan J.
Abstract: Ir‐catalyzed asymmetric alkene hydrogenation is presented as the strategy par excellence to prepare saturated isoprenoids and mycoketides. This highly stereoselective synthesis approach is combined with an established 13 C‐NMR method to determine the enantioselectivity of each methyl‐branched stereocenter. It is shown that this analysis is fit for purpose and the combination allows the synthesis of the title compounds with a significant increase in efficiency. Abstract : Cyclo ‐archaeol, iso ‐caldarchaeol, caldarchaeol, and mycoketide are prepared by employing asymmetric hydrogenation to generate the multiple stereocenters.